Facial mask-related acne during the coronavirus disease 2019 pandemic: a literature review - Handika, Natalia Jennifer (International Journal of Research in Medical Sciences, 2022)
The global COVID-19 pandemic has given rise to the need to use personal protective equipment such as masks, among healthcare professionals and the general public. Regular long time wearing of mask during this pandemic has resulted in increased incidence of acne flare, which the term maskne or mask acne has emerged. This literature review discussed current knowledge of maskne, the factors predisposing person to developing maskne, some strategies which may prevent maskne and its effects.